1996
DOI: 10.1103/physreva.53.1310
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Schrödinger equation and two-level atoms

Abstract: Starting with the same form of atomic nonlinearity Weinberg [1] and Wódkiewicz and Scully [2] obtained contradictory results concerning an evolution of the atomic inversion w in a two-level atom in Weinberg's nonlinear quantum mechanics: If the atom is initially in a ground state then either (1) the evolution of w can be linear if one uses a nonlinear generalization of the Jaynes-Cummings Hamiltonian, or (2) is always nonlinear if one uses the nonlinear Bloch equations derived from the nonlinear atomic Hamilto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 32 publications
(52 reference statements)
0
36
0
Order By: Relevance
“…It is argued that the nonlinear quantum evolution introduced by consciousness is logically consistent and may exist (Czachor, 1995;Shan, 2004a). In addition, we may use the definite non-linearity element in the complete evolution equation of matter to define the consciousness property of matter.…”
Section: A Quantum Effect Of Consciousnessmentioning
confidence: 99%
“…It is argued that the nonlinear quantum evolution introduced by consciousness is logically consistent and may exist (Czachor, 1995;Shan, 2004a). In addition, we may use the definite non-linearity element in the complete evolution equation of matter to define the consciousness property of matter.…”
Section: A Quantum Effect Of Consciousnessmentioning
confidence: 99%
“…An important drawback of such Hamiltonian generalizations is that we have to represent observables by nonlinear operators which leads to interpretational difficulties. To give an example, it is not clear which definition of a nonlinear eigenvalue is physically meaningful, or how to represent higher moments of experimentally measured random variables if nonlinear operators are involved (Czachor, 1996a). Let us therefore first consider what happens if H = H a ρ a = TrĤρ and S is an arbitrary (differentiable) function of the Casimirs C k .…”
Section: -Bracketmentioning
confidence: 99%
“…The physical problem turns out to be of the same type as the one with the definition of dynamics of composite systems given by Weinberg in [30] . The Weinberg definition not only led to the nowadays famous "faster-than-light telegraph" but also predicted an apparently paradoxical disagreement between the Bloch equation and Janes-Cummings approaches to two-level systems [31]. A corrected description [31] showed that the paradox is a result of a wrong formalism.…”
Section: Complete Positivity and Nonlinearitymentioning
confidence: 99%
“…The Weinberg definition not only led to the nowadays famous "faster-than-light telegraph" but also predicted an apparently paradoxical disagreement between the Bloch equation and Janes-Cummings approaches to two-level systems [31]. A corrected description [31] showed that the paradox is a result of a wrong formalism. It proved also that a precise way of describing noninteracting systems leads to a meaningful dynamics when the systems are coupled.…”
Section: Complete Positivity and Nonlinearitymentioning
confidence: 99%